2013
DOI: 10.1680/maen.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Shoreline change mapping along the coast of Galicia, Spain

Abstract: 2 3 4This study was concerned with shoreline change and cliff recession. Galicia (north-west Spain) comprises a very energetic and diversified coast. The study focused on the analysis of the coastal dynamics and the spatio-temporal changes of coastal morphology for the years 1956, 2003, 2006 and 2008, using the digital shoreline analysis system (DSAS) extension. Estimation of the rates of erosion and accretion along the pilot site (Fisterra/Finisterre area) was performed. In addition, a continuous coastline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
(37 reference statements)
1
6
0
3
Order By: Relevance
“…However, some previous works have obtained average retreat rates of 0.57 m year -1 for the period 2006-2017, reaching rates up to 1.22 and 2.19 m year -1 near the town of Luanco, in the surroundings of Peñas Cape (Domínguez-Cuesta et al, 2020a). Although these retreat values corresponds to specific areas, they are values similar to those obtained in Fisterra, Northern Spanish Atlantic coast (range 0.03 -2.78 m year -1 , Pérez-Alberti et al, 2013), much higher than the established in the central coast of Portugal (range 0.013 -0.130 m year -1 , Epifânio et al, 2013) or the Atlantic rocky coast (Gómez-Pujol et al, 2014 and references therein) and they agree with those reported in Holderness, considered the most active coast in Europe, with values of 2 m year -1 (Bird, 2008;Castedo et al, 2015;Hobbs et al, 2020).…”
Section: Introductionsupporting
confidence: 85%
“…However, some previous works have obtained average retreat rates of 0.57 m year -1 for the period 2006-2017, reaching rates up to 1.22 and 2.19 m year -1 near the town of Luanco, in the surroundings of Peñas Cape (Domínguez-Cuesta et al, 2020a). Although these retreat values corresponds to specific areas, they are values similar to those obtained in Fisterra, Northern Spanish Atlantic coast (range 0.03 -2.78 m year -1 , Pérez-Alberti et al, 2013), much higher than the established in the central coast of Portugal (range 0.013 -0.130 m year -1 , Epifânio et al, 2013) or the Atlantic rocky coast (Gómez-Pujol et al, 2014 and references therein) and they agree with those reported in Holderness, considered the most active coast in Europe, with values of 2 m year -1 (Bird, 2008;Castedo et al, 2015;Hobbs et al, 2020).…”
Section: Introductionsupporting
confidence: 85%
“…Different methods have been used to analyze changes in coastal areas [11][12][13][14][15]. However, the essential starting point for any study of this type is to define and delimit the shoreline to enable quantification of any changes that take place.…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos 20 años, se han elaborado trabajos que analizan el litoral gallego desde distintos puntos de vista, desde los que analizan la evolución de algún sector de la costa, caso de la Ría de Muros e Noia (Trenhaile et al, 1999); los que clasifican tipológicamente las costas (Gomez-Pazo y Perez-Alberti, 2016); los cambios que se han producido en la línea de costa a nivel general desde el Pleistoceno a la actualidad (Pérez-Alberti et al, 2013), o aquellos que analizan la movilidad de las costas rocosas (Pérez-Alberti y Trenhaile, 2015a; Pérez-Alberti y Trenhaile, 2015b) sin olvidar los análisis centrados en zonas sedimentarias de gran interés como el sistema de la barra arenosa/sistema playaduna de Rodas en las Illas Cíes (Costas et al, 2005(Costas et al, , 2009) o la comprensión de las secuencias sedimentarias en la costa cantábrica (Feal-Pérez et al, 2014). Sin embargo, no existe una investigación en la que se analice el grado de vulnerabilidad de la costa de Galicia ante los temporales o los posibles cambios ambientales.…”
Section: Introductionunclassified